Climate-Responsiveness Embodied in Modern Mosque Design - Era Nopera Rauzi; Izziah Hasan; Laina Hilma Sari (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2021)
Abstract: A mosque is a place of worship for Muslims. Modernity concept to visualize the simple form in a mosque is relevant, which would help the worshippers to be more solemn. Office buildings, mainly located in Aceh, known as Serambi Mekkah, are required to provide a mosque in the office environment. Since its concept transforms from traditional style to modern style, the mosque in the office area is designed in modernity. The study purposes of enabling climate-responsive principles in mosque design for achieving indoor thermal comfort. Even though without available power support. The design method approached problem-solving by creating the building friendly to the environment and achieving indoor thermal comfort. This study used trial and error through modeling appropriate to climate-responsiveness mosque design in the office area. Furthermore, this study would be continued in complex buildings, namely schools and offices, promoting environmentally-friendly to be applied in building design. Abstrak: Masjid adalah tempat ibadah bagi umat Islam. Konsep modernitas untuk memvisualisasikan bentuk sederhana di masjid adalah relevan, yang akan membantu jamaah untuk lebih khusyuk. Gedung perkantoran khususnya yang berada di Aceh yang dikenal dengan Serambi Mekkah wajib menyediakan mushola di lingkungan kantor. Karena konsepnya bertransformasi dari gaya tradisional ke gaya modern, masjid di area perkantoran juga didesain dengan gaya modern. Tujuan studi ini adalah untuk mengaktifkan prinsip responsif iklim dalam desain masjid untuk mencapai kenyamanan termal dalam ruangan meskipun tanpa dukungan daya yang tersedia. Metode desain pada studi ini menggunakanpendekatan pemecahan masalah untuk menciptakan bangunan ramah lingkungan dan mencapai kenyamanan termal dalam ruangan. Penelitian ini menggunakan metode trial and error melalui pemodelan yang sesuai dengan desain masjid yang responsif terhadap iklim di kawasan perkantoran. Selanjutnya studi ini akan dilanjutkan penerapannya pada bangunan kompleks seperti sekolah dan perkantoran untuk mempromosikan desain bangunan ramah lingkungan.